2002
DOI: 10.1002/jcp.10047
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gap junction intercellular communication by extremely low‐frequency electromagnetic fields in osteoblast‐like models is dependent on cell differentiation

Abstract: Electromagnetic fields have been used to augment the healing of fractures because of its ability to increase new bone formation. The mechanism of how electromagnetic fields can promote new bone formation is unknown, although the interaction of electromagnetic fields with components of the plasma membrane of cells has been hypothesized to occur in bone cells. Gap junctions occur among bone forming cells, the osteoblasts, and have been hypothesized to play a role in new bone formation. Thus it was investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Moreover, distribution of Cx43 between the cytoplasm and plasma membrane was unaffected. This result was dependent on the differentiation state of the cells in culture, since it was observed only in preconfluent, proliferating MC-3T3-E1, but not after the cells had become more differentiated, nor was it observed in ROS 17/2.8 cells 19,40. In this study, the expression of Cx43 was analyzed to assess the GJIC in hFOB 1.19 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, distribution of Cx43 between the cytoplasm and plasma membrane was unaffected. This result was dependent on the differentiation state of the cells in culture, since it was observed only in preconfluent, proliferating MC-3T3-E1, but not after the cells had become more differentiated, nor was it observed in ROS 17/2.8 cells 19,40. In this study, the expression of Cx43 was analyzed to assess the GJIC in hFOB 1.19 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the clinical application of EMF, its mechanism is still obscure. Previous studies suggested that bioeffects of EMF were related to the cells used (Lohmann et al, 2000(Lohmann et al, , 2003Santini et al, 2003;Sollazzo et al, 1997), their maturation (Aaron and Ciombor, 1996;Diniz et al, 2002;Yamaguchi et al, 2002), and the percentage of fetal calf serum in the culture medium (De Mattei et al, 2005;Sollazzo et al, 1997). The physical parameters of the exposure unit are very crucial (Aaron et al, 1999;Fitzsimmons et al, 1989;Katsir et al, 1998), but there are little comparative results between different EMF signals.…”
Section: Introductionmentioning
confidence: 96%
“…Extremely low frequency magnetic fields can initiate a number of biochemical and physiological alterations in biological systems of different species (8)(9)(10)(11)(12). Many of these effects have been associated with free-radical production (13,14).…”
mentioning
confidence: 99%